Pathology, Radiology, and Genetics of Interstitial Lung Disease in Patients With Shortened Telomeres. (July 2021) - Cecchini, Matthew J.; Tarmey, Tara; Ferreira, Allison; Mangaonkar, Abhishek A.; Ferrer, Alejandro; Patnaik, Mrinal M.; Wylam, Mark E.; Jenkins, Sarah M.; Spears, Grant M.; Yi, Eunhee S.; Hartman, Thomas E.; Scott, John P.; et al.
Abstract : Interstitial lung diseases (ILDs) in patients with shortened telomeres have not been well characterized. We describe demographic, radiologic, histopathologic, and molecular features, and p16 expression in patients with telomeres ⩽10th percentile (shortened telomeres) and compare them to patients with telomere length >10th percentile. Lung explants, wedge biopsies, and autopsy specimens of patients with telomere testing were reviewed independently by 3 pathologists using defined parameters. High-resolution computed tomography scans were reviewed by 3 radiologists. p16-positive fibroblast foci were quantified. A multidisciplinary diagnosis was recorded. Patients with shortened telomeres (N=26) were morphologically diagnosed as usual interstitial pneumonia (UIP) (N=11, 42.3%), chronic hypersensitivity pneumonitis (N=6, 23.1%), pleuroparenchymal fibroelastosis, fibrotic nonspecific interstitial pneumonia, desquamative interstitial pneumonia (N=1, 3.8%, each), and fibrotic interstitial lung disease (fILD), not otherwise specified (N=6, 23.1%). Patients with telomeres >10th percentile (N=18) showed morphologic features of UIP (N=9, 50%), chronic hypersensitivity pneumonitis (N=3, 16.7%), fibrotic nonspecific interstitial pneumonia (N=2, 11.1%), or fILD, not otherwise specified (N=4, 22.2%). Patients with shortened telomeres had more p16-positive foci ( P =0.04). The number of p16-positive foci correlated with outcome ( P =0.0067). Thirty-nine percent of patients with shortened telomeres harbored telomere-related gene variants. Among 17 patients with shortened telomeres and high-resolution computed tomography features consistent with or probable UIP, 8 (47.1%) patients showed morphologic features compatible with UIP; multidisciplinary diagnosis most commonly was idiopathic pulmonary fibrosis (N=7, 41.2%) and familial pulmonary fibrosis (N=5, 29%) in these patients. In conclusion, patients with shortened telomeres have a spectrum of fILDs. They often demonstrate atypical and discordant features on pathology and radiology leading to diagnostic challenges. Abstract : Supplemental Digital Content is available in the text.